The educational character on instruction - Abdul Rasyid, Happy Fitria, Muhammad Kristiawan, (Opción, 2019)
In this paper, we aimed at obtaining data on the implementation of educational character to develop the characteristics of students in SMK (Vocational School) PGRI Tanjung Raja and how many students were in the good category, enough category and less category. We used a qualitative method in this paper. As a result, the students in the good category were 131 students or 65.5%; enough category were 59 students or 29.5%; and less category were 10 students or 5%. So it can be concluded that the tendency of the behavior of students’ character values of SMK PGRI Tanjung Raja was good.